Analisis Pengaruh Dana Pihak Ketiga, Inflasi, Non Performing Loan Dan Loan To Deposit Ratio Terhadapkredit Modal Kerja Pada Bank Umum Di Jawa Timur - venny Atika Qomariyah; Niniek Imaningsih (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
Banks are financial institutions that accommodate funds from the public in the form of savings and return them in the form of credit to those in need in order to improve people's lives. Banks also do three other things: collect funds, send money or transfer money, and provide other financial services. Working Capital Credit is a credit facility from a financial institution that is extended to business actors to finance their production and operational activities so that they can expand their business. Through the provision of working capital loans, it is expected to grow the economy. This study shows the results that Third Party Funds have a positive and significant influence on Distribution of Working Capital Loans to Commercial Banks in East Java. Inflation has no positive and insignificant effect on Distribution of Working Capital Loans at Commercial Banks in East Java.Non Performing Loan does not have a positive and insignificant influence on Distribution of Working Capital Loans at Commercial Banks in East Java.Loan to Deposit Ratio has a positive and significant effect on Distribution of Working Capital Loans to Commercial Banks in East Java. Keywords: Third Party Funds, Inflation, Non Performing Loans, Loan To Deposit Ratio, Working Capital Loans